PENGARUH PEMADATAN BETON SEGAR TERHADAP KUAT TEKAN BETON - Lina Flaviana Tilik; Ika Sulianti (Politeknik Negeri Sriwijaya, 2012)
Concrete is construction material which frequently used in the field of civil engineering. In constructing process, concrete material is a part of building structure with some superiorities, among others, are: high compressive strength, being able to be formed as needed, no serious maintenance needed, and relatively fireproof and weatherproof. Various studies and experiments in the field of concrete as part of efforts to improve the quality of concrete. One way to increase the strength of concrete is to increase the compacting, which minimizes pores or cavities formed in the concrete. The additive material used in this study is fly ash. Fly ash is a waste of coal burning. The fly ash in this study was taken from PLTU Bukit Asam Tanjung Enim. The type of fly ash used is fly ash F class, which is the result of burning of coal of anthracite/bituminous with low content of CaO, less than 10%. Maximum density of concrete can be attained by compacting the fresh concrete. The main goal of compaction of the fresh concrete is to eliminate air cavities and to achieve maximum density. The concrete compressive strength will increase if the density of concrete also increases. The compaction of 75 kg / cm ² with no fly ash added generates the strength of compressive of concrete 41.08 MPa. The greater compaction of fresh concrete is given, the more compacted the concrete will be, surely the weight of the concrete content will get heavier. This is because the concrete that has been compacted will be more compacted, so that air pores in the concrete will be smaller than normal concrete. The maximum weight of concrete of compaction 75 kg / cm ² with no fly ash added is 2.518 ton / m³. In this study the crack tend to form columnar type.